2019
DOI: 10.1111/ced.13925
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features of Chinese patients with lichen and macular primary localized cutaneous amyloidosis

Abstract: Summary Background Primary localized cutaneous amyloidosis (PLCA) is a chronic pruritic skin disorder. The genetic basis of familial (f)PLCA involves mutations in the oncostatin M receptor (OSMR) and interleukin‐31 receptor A (IL31RA) genes, but the disease pathophysiology is not fully understood. Aim To investigate the OSMR mutation spectrum in patients with sporadic (s)PLCA/fPLCA, lichen/macular PLCA in mainland China. Methods This study was carried out on 64 patients with sPLCA, along with 36 with fPLCA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This process can last from weeks to years, but once the first amyloid aggregation is formed, the development of the insoluble architecture soon follows [2]. With that said, the exact pathogenesis remains unclear, but it is considered to be multifactorial with both genetic and environmental risk factors associated with keratinocyte-derived amyloid formation [3].…”
Section: Treatment Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process can last from weeks to years, but once the first amyloid aggregation is formed, the development of the insoluble architecture soon follows [2]. With that said, the exact pathogenesis remains unclear, but it is considered to be multifactorial with both genetic and environmental risk factors associated with keratinocyte-derived amyloid formation [3].…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Primary localized cutaneous amyloidosis appears to be mainly sporadic but in about 10% of patients, an autosomal dominant inheritance pattern with variable penetrance can be observed [4]. In addition, PLCA is common in southeast Asia, South America, and the middle eastern region [3]. The racial susceptibility and familial aggregation suggest that underlying genetic factors must play a role in the pathogenesis of PLCA.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Recently, we demonstrated that the c.1538G>A (p.G513D) and c.2081C>T (p.P694L) mutations of OSMR were the most frequent mutations in a Chinese PLCA population (Lu et al, 2019 ). It has been reported that OSM maintains hair follicle stem cell and muscle stem cell quiescence by binding to heterodimeric receptors comprising gp130 and OSMRβ (Sampath et al, 2018 ; Wang et al, 2019 ).…”
mentioning
confidence: 99%
“…These are thought to arise from degenerate protein from basal keratinocytes, immunoglobulins and normal serum amyloid P component. Most cases are sporadic, with autosomal dominant inheritance responsible for about 10% of cases, and although common in South American and Asian populations, PLCA is rare in white populations.…”
mentioning
confidence: 99%
“…Mutations in the genes for oncostatin M receptor ( OSMR ) and interleukin‐31 receptor A ( IL31RA ) have been previously reported in patients with PLCA . OSMR encodes for OSMR‐β, a member of the IL‐6 type cytokine receptor family, which binds IL‐31 and oncostatin M (OSM).…”
mentioning
confidence: 99%